Effectiveness of international virtual training on biorisk management in the context of COVID-19 - Qasmi, Shamsul Arfin; Standley, Claire; Mohsin, Saima; Sarwar, Samreen; Malik, Laila; Aziz, Fatima (Frontiers in Public Health, 2022)
Introduction The COVID-19 pandemic has resulted in enormous increases in laboratory activities to keep pace with diagnostic testing and research efforts. However, traditional training, technical assistance, and capacity-building approaches were disrupted by the travel and movement restrictions put in place to control the spread of the disease. To address the needs of laboratorians and managers to conduct laboratory activities safely and securely during the pandemic, a highly interactive virtual training (IVT) workshop on biorisk management during COVID-19 was conducted through active learning strategies that connected speakers with participants. The objective of the training was to increase the basic knowledge and standards of biosafety and biosecurity practices, risk assessment, and control measures with reference specifically to the context of the COVID-19 pandemic and apply a rigorous evaluation methodology to assess the effectiveness of the IVT. The training covered a broad range of topics and encompassed national to international guidelines. Methods Participants were selected through official channels at the national level, focusing on institutions within Pakistan. The sessions included lectures from international experts in biorisk management concepts, and incorporated poll questions as well as pre- and post-tests and feedback on the speakers' knowledge and presentation skills, to increase interactivity. The pre- and post-test comprised similar multiple-choice questions and provided to every participant to ascertain the impact of the training on awareness and knowledge of biorisk management topics and concepts, and results were compared using paired t-tests. For feedback on the speakers, participants were asked to submit their ratings measured on a five-point Likert scale. The reliability of the Likert scale was estimated using Cronbach's alpha. Analyses were performed using Microsoft Excel and SPSS version 23. Results In total, 52 individuals from different laboratories across Pakistan and Pakistani students from abroad (China) as well participated in at least one session of the IVT. The participants' pre- and post-test scores showed a significant increase in knowledge and awareness (p < 0.001). The obtained Cronbach's alpha score was >0.8, indicating high reliability of the generated feedback on the IVT approach and speakers. Conclusion The IVT on biosafety and biosecurity in the context of the COVID-19 pandemic proved beneficial for laboratory professionals and could be a useful model to continue in the future for raising awareness and knowledge.